2011
DOI: 10.1007/s11136-011-0023-4
|View full text |Cite|
|
Sign up to set email alerts
|

Understanding appraisal processes underlying the thentest: a mixed methods investigation

Abstract: Ipsative and normative discrepancy scores measure distinct constructs, represent different configurations of appraisal change, and are not invalidated or explained by recall bias. The thentest does not imply recalibration alone but rather a host of health- and self-care-related concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…However, we showed that not only recalibration, but also reprioritization simultaneously contributed to observed changes, as our method was, as compared to previous studies, more comprehensive, combining all aspects of response shift in a single quantitative model. Future studies should directly compare the traditional then-test with the structural equation modeling method to examine the hypothesis that the then-test is not only capturing recalibration effects, but also those of reprioritization [5,21].…”
Section: Discussionmentioning
confidence: 99%
“…However, we showed that not only recalibration, but also reprioritization simultaneously contributed to observed changes, as our method was, as compared to previous studies, more comprehensive, combining all aspects of response shift in a single quantitative model. Future studies should directly compare the traditional then-test with the structural equation modeling method to examine the hypothesis that the then-test is not only capturing recalibration effects, but also those of reprioritization [5,21].…”
Section: Discussionmentioning
confidence: 99%
“…In studies of diverse patient populations, this tool has documented differences in patterns of emphasis between people who fare better, fare worse, or have a variable course with multiple sclerosis (MS) [ 4 ], after spinal surgery [ 8 ], or before [ 25 ] and after invasive cancer treatment [ 26 , 27 ]. It has documented differences in key indicators of clinically important change, suggesting that interpretation of change over time depends on many factors beyond post-minus-pre scores [ 28 ]. Next-generation appraisal measures focused on reducing the need to code text generated from open-ended questions.…”
Section: Introductionmentioning
confidence: 99%
“…However, research has demonstrated that the method is con-founded by recall bias 2,60 and implicit theories of change, 41 and only a small proportion of the scores reflect recalibration response shift. 57 Consequently, the then-test is no longer commonly used for detecting response shift.…”
Section: Response Shift Research In Spine Surgerymentioning
confidence: 99%